Conservation View point-About Wastelands - Bali, J.S. (Journal of Soil and Water Conservation, 2022)
In the government circles of most developing countries, and especially so in India, an idea goes through three stages. When an expert says it, it is dubbed as "impractical"; when more experts advocate it, it is held back as "costly"; but when the 'Minister is won over, it is hailed as '`obvious, we always said so". It is a matter of great satisfaction that the water harvesting idea now reached the third stage. Now, the Prime Minister has said it. The 26th January Newspapers advertised water harvesting as the "Golden Jubilee of Indian Republic" idea. A hundred-thousand soil and water conservationists of the country must feel a sense of achievement as they have been the votaries of water harvesting for decades now. But as Vivekananda exhorted to Indians: "Think a little less, and act a little more", there is need to translate this thought into a massive programme for rural India, about 90 million hectares of whose land are dependent upon rainfall to grow any plants and provide livelihood to the seventy percent population.